2005
DOI: 10.1055/s-2005-872172
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity versus Reactivity - Recent Advances in RuO4-Catalyzed Oxidations

Abstract: Since its introduction into organic chemistry more than fifty years ago, RuO 4 has been used mainly as a strong oxidizing agent. Owing to its high reactivity, catalytic reactions employing RuO 4 were often considered to be sluggish or unselective. However, within the past ten years, several groups have reported the development of new and selective oxidative transformations possible only under RuO 4 catalysis. The present article summarizes the state of research in this field and tries to give a systematic over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
78
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(84 citation statements)
references
References 52 publications
5
78
0
1
Order By: Relevance
“…Previous findings related to the RICO mechanism for PAH oxidation suggested that C−C bond scission is involved in the first step of the reaction. Plietker suggested that the mechanism may be similar to the oxidative cleavage of double bonds, in which RuO 4 adds to a double bond to form a ruthenium(VI) compound . Frenking and co‐workers have used DFT calculations to show that RuO 4 will form stable ruthenium(VI) adducts with ethene through a [3+2] cycloaddition of RuO 4 across the double bond .…”
Section: Introductionmentioning
confidence: 99%
“…Previous findings related to the RICO mechanism for PAH oxidation suggested that C−C bond scission is involved in the first step of the reaction. Plietker suggested that the mechanism may be similar to the oxidative cleavage of double bonds, in which RuO 4 adds to a double bond to form a ruthenium(VI) compound . Frenking and co‐workers have used DFT calculations to show that RuO 4 will form stable ruthenium(VI) adducts with ethene through a [3+2] cycloaddition of RuO 4 across the double bond .…”
Section: Introductionmentioning
confidence: 99%
“…The furan ring can be oxidized to the corresponding carboxylic acid by the action of ozone or ruthenium tetroxide, the latter being generated from hydrated ruthenium (III) chloride or ruthenium (IV) oxide [21] Ruthenium tetroxide is formed in situ from RuCl 3 or RuO 2 by using an appropriate oxidant such as NaIO 4 , KIO 4 , NaClO, NaBrO 3 , Ce(SO 4 ) 2 , K 2 S 2 O 8 , Oxone ® or H 5 IO 6 [22] thus allowing the use of the precursor ruthenium derivative in a catalytic amount (Scheme 3) [23]. The reaction takes place in the interfacial area of a biphasic system carbon tetrachloride:water.…”
Section: Furan As C-1 Synthonmentioning
confidence: 99%
“…1) Ruthenium tetroxide (RuO 4 ) is well known as a highly effective oxidant, [2][3][4] and the oxidative cleavage of simple CϭC bonds is one of the most common reactions between RuO 4…”
mentioning
confidence: 99%
“…This chemistry has been extensively studied. 1) Ruthenium tetroxide (RuO 4 ) is well known as a highly effective oxidant, [2][3][4] and the oxidative cleavage of simple CϭC bonds is one of the most common reactions between RuO 4 2) and alkenes. However, only a low effort regarding the oxidative cleavage of the CϭC double bond to the corresponding carbonyl compounds in enol ethers, enol esters and enamines has been made to date.…”
mentioning
confidence: 99%